Antidiabetic and hypolipidemic activities of eburicoic acid, a triterpenoid compound from Antrodia camphorata, by regulation of Akt phosphorylation, gluconeogenesis, and PPARα in streptozotocin-induced diabetic mice. Issue 37 (5th June 2018) - Lin, Cheng-Hsiu; Kuo, Yueh-Hsiung; Shih, Chun-Ching
Abstract : The study is designed to examine the potential effects and underlying mechanisms of eburicoic acid (TRR), a compound from Antrodia camphorata, in streptozotocin (STZ)-induced diabetic mice. Abstract : The study is designed to examine the potential effects and underlying mechanisms of eburicoic acid (TRR), a compound from Antrodia camphorata, in streptozotocin (STZ)-induced diabetic mice. Diabetic mice were randomly divided into six groups and given TRR orally by gavage (at three dosage rates) or fenofibrate (Feno) (250 mg kg −1 body weight) or metformin (Metf) (300 mg kg −1 body weight) or vehicle for 2 weeks. STZ-induced diabetic mice were found to have increased blood glucose, HbA1C, plasma triglyceride (TG) and total cholesterol (TC) levels, but reduced blood insulin, adiponectin, and leptin levels as compared with the CON group. TRR was found to lower blood glucose and HbA1C, but increase insulin levels. Plasma TG and TC levels were significantly lowered in TRR, Feno, or Metf-treated STZ-induced diabetic mice as compared with the vehicle-treated STZ group, indicating that TRR, Feno, and Metf ameliorated hyperlipidemia. The islet cells of STZ-induced diabetic mice exhibited a marked reduction from their classic round-shape as compared to the CON mice. The TRR-treated STZ mice revealed restoration of the size of Langerhans islet cells with β-cell repair as compared with the vehicle-treated STZ mice, implying that TRR ameliorated STZ-induced diabetic states within the pancreas. STZ-induction was found to decrease the expressions of membrane glucose transporter 4 (GLUT4), and phosphorylation of Akt in skeletal muscles, and administration of TRR reversed all the decreases. Moreover, administration of TRR increased blood insulin levels and enhanced hepatic expression levels of phospho-Akt and phospho-FoxO1 but decreased the mRNA levels of glucose-6-phosphatase (G6 Pase) and phosphoenolpyruvate carboxykinase (PEPCK) to suppress hepatic glucose production, thus leading to TRR's antidiabetic activity. Additionally, TRR caused an increase in the expression levels of fatty acid oxidation gene peroxisome proliferator-activated receptor α (PPARα), but a decrease in lipogenic fatty acid synthase (FAS) and PPARγ expressions in the liver. TRR treatment suppressed hepatic mRNA levels of sterol regulatory element binding protein (SREBP) 1c and SREBP2, leading to decreased plasma triglyceride and total cholesterol levels. These findings indicate that TRR may effectively enhance therapeutic potential in the treatment of type 1 diabetes mellitus and/or hyperlipidemia.